Cloning and biochemical characterization of CG16936, a putative glutathione transferase in Drosophila Melanogaster / Tanusya Murali - Murali, Tanusya (2014)

(untitled)
CG16936, which was classified as DmGSTE12 was studied in this project. This study cloned and expressed CG16936 and the resulting recombinant CG16936 has been reactive towards 1,2-dichloro-4-nitrobenze (DCNB) (0.4324 μmol/min/mg) but of no activities towards, 1-chloro-2,4-nitrobenzene, trans-2-hexenal, p-nitrobenzyl chloride (NBC), ethacryanic acid (EA), trans-4-phenyl-butene-2-one (PBO), hexa-2,4-dienal, trans,trans-hepta-2,4-dienal, 1,2-epoxy-3-p-nitrophenoxy propane (EPNP), bromosulfophthalein (BSP) and trans-oct-2-enal. In previous work, it was shown that CG16936 was expressed in response to odorant treatment to fruit flies. Our work investigated the direct contribution of the recombinant CG16936 towards conjugation of odorants Glutathione (GSH). No evidence of conjugated product yielded when the recombinant protein acted upon GSH and trans-2-hexenal on thin layer chromatography. The absence of enzymatic activity hence suggested the inability of CG16936 to conjugate t-2-hexenal to GSH. Upon exposure to benzaldehyde, expression of CG16936 was demonstrated unchanged. The evidences suggested that CG16936 could have assumed other physiological function other than detoxification of odorant and its direct involvement in oxidative stress.